Análise dos conceitos de autonomia e responsabilidade e o contexto da agência artificial - Leal, Franciele da Silva [UNESP] (2016)
In this work, we propose to develop a critical analysis of the concepts of agency and responsibility in the contemporary technological context in which artificial systems said to be autonomous are produced. Aiming on this goal, we present, firstly, some theories of action, and we problematize the notions of causal event and causal action, object and agent, aiming on clarifying the notion of agency. Following, we analyze the notion of responsible action proposed by Hans Jonas, once he proposes a notion of responsibility considering the contemporary technological development. In particular, we present and discuss the heuristic notion of fear proposed by Jonas (2004) whose goal is to create possible scenarios which may anticipate long-term implications of the use of new technologies and may help to inform society about the possible consequences of their use for the new generations. Finally, we deal more specifically with the legitimacy of the attribution of agency and responsibility to artificial systems, specially robots, from the perspective of Philosophy and Robotics, from theses defended by Hans Jonas (2004, 2013) and Willem Haselager (2005). In their texts, both authors discuss the possibility of attributing agency and responsibility to artificial systems capable of learning and making decisions which surpass the limits of their initial programming. We conclude that it seems problematic both to attribute agency to autonomous artificial systems in the same sense in which human beings are considered to be agents, and to reduce such systems to mere causally determined objects.